2014
DOI: 10.1038/ajg.2013.427
|View full text |Cite
|
Sign up to set email alerts
|

Host and Viral Determinants of the Outcome of Exposure to HCV Infection Genotype 4: A Large Longitudinal Study

Abstract: IL-28B-CC genotype, multispecific HCV T-cell responses, rapid decline in ALT, and viral load predict spontaneous clearance and response to acute HCV-G 4 therapy. IL-28B-CC genotype correlates with developing early multispecific T-cell responses. These findings have important implications for predicting the outcome of HCV exposure and acute infection and identifying patients likely to benefit from therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 54 publications
1
9
0
Order By: Relevance
“…Further, Thomas et al44 showed that the SNP rs12979860 upstream of IL28B and the C/C genotype were associated with spontaneous clearance of HCV, and this finding was confirmed by recent studies in patients with acute HCV 37,41. Interestingly, jaundice during acute infection was more common in patients with the C/C genotype 24,46. The T/T genotype occurred more often in people of African descent, had an intermediate frequency among Europeans, and a lower frequency among Asians, a finding that partly explains the ethnic differences seen in spontaneous acute HCV recovery rates across different ethnic groups.…”
Section: Acute Hepatitis C: An Emerging Field Of Pharmacogeneticsmentioning
confidence: 82%
See 4 more Smart Citations
“…Further, Thomas et al44 showed that the SNP rs12979860 upstream of IL28B and the C/C genotype were associated with spontaneous clearance of HCV, and this finding was confirmed by recent studies in patients with acute HCV 37,41. Interestingly, jaundice during acute infection was more common in patients with the C/C genotype 24,46. The T/T genotype occurred more often in people of African descent, had an intermediate frequency among Europeans, and a lower frequency among Asians, a finding that partly explains the ethnic differences seen in spontaneous acute HCV recovery rates across different ethnic groups.…”
Section: Acute Hepatitis C: An Emerging Field Of Pharmacogeneticsmentioning
confidence: 82%
“…In a recent study24 of a well characterized cohort of acute HCV patients, we showed that a decrease in alanine aminotransferase within 4 weeks (odds ratio [OR] 6.83; P <0.0001), jaundice (OR 3.54; P =0.001), female sex (OR 2.39; P =0.007), and a >2.5 log 10 decrease in HCV-RNA within 8 weeks (OR 2.48; P =0.016) were independently associated with spontaneous clearance. IL28B CC was also associated with a multispecific T-cell response ( r 2 =0.0.835; P <0.001).…”
Section: Acute Hepatitis C: An Emerging Field Of Pharmacogeneticsmentioning
confidence: 94%
See 3 more Smart Citations